Correlation of constitutive photomorphogenic 1 (COP1) and p27 tumor suppressor protein expression in ovarian cancer - Ko, Eun-Ji; Oh, Young Lim; Kim, Heung Yeol; Eo, Wan Kyu; Kim, Hongbae; Kim, Ki Hyung; Koh, Suk Bong; Ock, Mee Sun; Choi, Yung Hyun; Kim, Ari; Choi, Hyun Ho; Park, Eun Joo; et al. (Genes & genomics, 2019)
Background Constitutive photomorphogenic 1 (COP1) is an E3 ubiquitin ligase that regulates important target proteins for cell growth including p27. The tumor suppressor p27 negatively regulates the cell cycle by inhibiting cyclin-dependent kinase. COP1 negatively regulates p27 stability by mediating its nuclear export and degradation. Objective Even if COP1 and p27 are tightly related and have significant roles in tumor progression, the expression patterns and relationship of both proteins in cancer have not yet been studied. Method We analyzed the expression patterns and relationship between COP1 and p27 using an ovarian cancer tissue microarray by dual immunofluorescence analysis. Results The expression levels of COP1 and p27 proteins were not significantly different between ovarian cancer tissue and normal control tissue. Other clinical data including age, tumor type, tumor grade, and stage were not significantly related to expression of the two proteins. The co-relationship between COP1 and p27 proteins was significantly high (Pearson correlation coefficient 0.79, p = 8.65 × 10 −22 ). Conclusions Our results demonstrate that while the expression levels of COP1 and p27 are highly correlated, they are not significantly related to cancer progression in ovarian cancer.